Показники козиного молока в залежності від сезону року і періоду лактації - Зажарська, Надія Миколаївна; Zazharska, Nadiia; Костюченко, Катерина Геннадіївна; Kostiuchenko, Kateryna (Нац. наук. центр «Ін-т експериментальної і клінічної вет. медицини» НААН України, 2017)
The aim was to investigate changes of goat milk depending on the season and lactation period. Researches were conducted in the laboratory at Department of parasitology and veterinary and sanitary examination at Dnepropetrovsk State Agrarian and Economic University in 2013–2015. Були проведені моніторингові дослідження молока від 8 кіз із села Мар’янське Апостолівського району Дніпропетровської області (всього 211 проб) з 2013 р. по 2015 р. Були проаналізовані зміни показників жиру, білка та кількості соматичних клітин у молоці кіз за сезонами року. Вивчали розподіл соматичних клітин у порціях молока підчас доїння, а також у залежності від періоду лактації
Рarameters of goat milk depending on the season and lactation period
The aim was to investigate changes of goat milk depending on the season and lactation period. Researches were conducted in the laboratory at Department of parasitology and veterinary and sanitary examination at Dnepropetrovsk State Agrarian and Economic University in 2013–2015. Monitoring study of the milk from 8 goats from the village Mar’yanske, Apostol district of Dnepropetrovsk region were conducted (total 211 samples). The biochemical indexes of milk were determined by means of ultrasonic analyzer of milk of «Ekomilk type MILKANA KAM 98-2a».The amount of somatic cells was determined by means of viscometric analyzer «SOMATOS-M». Fat, protein and somatic cell count of goat milk for the seasons were determined. Somatic cells count in goat milk depending on lactation period, portions of milk during milking were studied. Also the daily milk yield was determined in august 2014. The protein of goat milk in autumn significantly increased compared to the summer and spring parameters (P<0.001). The fat content in summer was less than spring index by 33.7 % (P<0.001), autumn – by 16.3 % (P<0.01), winter – by 43.1 % (P<0.05). In autumn and winter the amount of somatic cells was 3.7 and 5 times accordingly more than the spring-summer figure (P<0.01). In the first month of lactation goat milk contained very low somatic cells count from 33 to 107 thousands / ml. Low and rather constant somatic cells count (15 to 63 thousands/ml) was marked in milk of goats during first lactation, though it lasted only seven months. A clear pattern of distribution of somatic cells in milk portions during milking was not detected. During the year, milk production increased in May and September, decreased in summer – because of the heat, and at the end of lactation – in 7-9 months. Були проведені моніторингові дослідження молока від 8 кіз із села Мар’янське Апостолівського району Дніпропетровської області (всього 211 проб) з 2013 р. по 2015 р. Були проаналізовані зміни показників жиру, білка та кількості соматичних клітин у молоці кіз за сезонами року. Вивчали розподіл соматичних клітин у порціях молока підчас доїння, а також у залежності від періоду лактації. Вимірювали добовий надій молока кіз на серпень 2014 року. Вміст білку в козиному молоці восени суттєво збільшувався по відношенню до літнього і весняного показників (Р<0,001). Виявлено, що жирність влітку менша весняного показника на 33,7 % (Р<0,001), осіннього – на 16,3 % (Р<0,01), зимового – на 43,1 % (Р<0,05). Восени та взимку кількість соматичних клітин у 3,7 і 5 разів відповідно більша весняно-літнього показника (Р<0,01). У перший місяць лактації молоко кіз містило дуже низьку кількість соматичних клітин від 33 до 107 тис./мл. Низький і досить постійний вміст соматичних клітин (від 15 до 63 тис/мл) відмічений в молоці кіз-первісток, хоч і перша лактація в них продовжувалася тільки 7 міс.
Keywords: козине молоко; goat milk; кількість соматичних клітин; somatic cells count; жир; fat; білок; protein; надій; yield; сезон; season; період лактації; lactation period